Optineurin in ocular herpes infection. (June 2022) - Grinage, Earon; Shukla, Deepak
Abstract: Herpes Simplex Virus-1 (HSV-1) is a neurotropic virus that can infect humans in the eye and travel to the trigeminal ganglion to establish latency. HSV-1 causes various disease states in both the primary and secondary sites of infection including the eye and the nervous system. This DNA virus exploits various adaptive measures to infect host cells, hijack host cell proteins, evade host immune response and spread from cell-to-cell to avoid immune detection. Recent data suggest that Optineurin (OPTN), a host protein, is a key restriction factor that prevents cell-to-cell spread of HSV-1 and guards against serious damage to the nervous system during infection. In recent years OPTN has gained increased attention because of its involvement in cellular mechanisms that promote homeostasis and prevent neurodegeneration. At the center of it all is the role OPTN plays as a receptor for selective autophagy. This review summarizes our latest understanding of the viral lifecycle, disease pathologies, and OPTN-mediated protective mechanisms during HSV-1 infection of the eye and the nervous system. We specifically highlight recent discoveries that implicate OPTN as crucial in the prevention of ocular and neurodegenerative diseases. Highlights: Herpes simplex virus (HSV) is a leading cause of infection-associated blindness. It is a DNA virus capable of replicating in the nuclei of virtually all ocular cell types. The virus exploits several different cellular proteins to establish a productive infection. Optineurin, a selective autophagy receptor, is required for maintaining ocular homeostasis. Optineurin is required for protection against HSV-induced nerve damage in the eye and the brain.